Hegemoni Ideologi dalam Lirik Tembang Dolanan Sunan di Indonesia - Dian Karina Rachmawati; Dwiki Ayu Pramudya (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2022)
Playing-songs (tembang dolanan) are songs for children as game accompaniment. This study aims to reveal the ideological hegemony contained in the lyrics of Sunan Giri playing-song and the moral leadership structure of Sunan Giri's character in preaching. The theory used is Hegemony by Gramsci and Metaphor by Pierce. This research used a qualitative description method. The reaearch object is the lyrics of Sunan Giri playing-song. The results of this study shows that the lyrics of Sunan Giri playing-song contains the hegemony of religious ideology. The concept of hegemony of ideology as outlined in the lyrics of "Cublek – Cublek Suweng" is an ideology of advice in seeking wealth, "Padhang Bulan" contains the hegemony of Islam as an explanation, and "Gambang Suling" contains hegemony of tactics in balancing life. The ideology makes the lyrics more comprehensive, easy to interpret and applicative.